Historicising ‘Irregular’ Migration from Senegal to Europe - Maher, Stephanie (Anti-Trafficking Review, 2017)
Contemporary discourses on migration from West Africa to Europe tend to frame migrants as victims of syndicated trafficking cartels that truck in human desperation. As part of this narrative, migrants are increasingly portrayed as ‘modern-day slaves’ in need of humanitarian protection. In both media and policy circles, African migrants are commonly referred to as desperate travellers who fall prey to exploitative ‘slave traders’ on their clandestine journeys to Europe. And yet, such framings do not adequately account for the ways in which migration from West Africa to Europe has a long and profound history, and thus does not sufficiently correspond to histories of enslavement. Nor do such framings appreciate how contemporary movements within and outside West Africa are informed by interrelated political genealogies that tie Europe to Africa in mutually dialectic ways. Focusing on the case of Senegal, this article aims to disrupt the ‘migrant as slave’ narrative by looking back at the histories of regional and international mobility that continue to shape population movements out of Senegal today.